2019
DOI: 10.3390/su11092710
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Reverse Logistics Network Design Considering Multi-Level Investments for Facility Reconstruction with Environmental Considerations

Abstract: Reverse logistics is convincingly one of the most efficient solutions to reduce environmental pollution and waste of resources by capturing and recovering the values of the used products. Many studies have been developed for decision-making at tactical, practical, and operational levels of the reverse supply chain. However, many enterprises face a challenge that is how to design the reverse logistics networks into their existing forward logistics networks to account for both economic and environmental sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Therefore, the value of ω 1 has minimal effect on the final optimization result of the model. This is consistent with the conclusion drawn in the literature [15,47]. Their research results indicated that the reduction in economic costs inevitably leads to an increase in carbon emissions.…”
Section: Cost and Environmental Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, the value of ω 1 has minimal effect on the final optimization result of the model. This is consistent with the conclusion drawn in the literature [15,47]. Their research results indicated that the reduction in economic costs inevitably leads to an increase in carbon emissions.…”
Section: Cost and Environmental Analysissupporting
confidence: 92%
“…Hao Yu and Wei Deng Solvang [4] presented a stochastic mixed integer programming model for designing and planning a generic multi-source, multi-echelon, capacitated, and sustainable reverse logistics network for WEEE management under uncertainty. Xuehong Gao [15] designed a novel stochastic reverse logistics network by reconstructing the facilities based on the existing forward logistics network. Kannan et al [16] built an RL network design model based on carbon footprint, which can be applied to real-time case studies, such as the tire, battery, and bottling industries.…”
Section: Reverse Logistics Network Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last two decades, quantitative optimization models and computational methods have been extensively investigated in order to improve the decision-making on reverse logistics network design at both strategic and operational levels [22,24]. With the implementation of different techniques, these decision-support models focused mainly on the optimization of economic efficiency [25][26][27][28], environmental impact [23,[28][29][30], potential job creation as well as other socio-economic impact factors [31]. The effectiveness of these optimization models and computational methods have been validated in a large variety of industries and business sectors [32][33][34][35].…”
Section: Reverse Logistics Models For Medical Wastementioning
confidence: 99%
“…Reverse logistics is convincingly one of the most efficient solutions to reduce environmental pollution and waste of resources by capturing and recovering the values of the used products [94]. Legislation, social image, corporate citizenship, and market competence force enterprises to integrate RL into their supply chains [95].…”
Section: Real-world Application Areas and Practicesmentioning
confidence: 99%